Multiple copy number variants in a pediatric patient with Hb H disease and intellectual disability. Issue 4 (11th January 2016) - Scheps, Karen G.; Francipane, Liliana; Nevado, Julián; Basack, Nora; Attie, Myriam; Bergonzi, María Fernanda; Cerrone, Gloria E.; Lapunzina, Pablo; Varela, Viviana
Abstract : Two distinct syndromes that link α‐thalassemia and intellectual disability (ID) have been described: ATR‐X, due to mutations in the ATRX gene, and ATR‐16, a contiguous gene deletion syndrome in the telomeric region of the short arm of chromosome 16. A critical region where the candidate genes for the ID map has been established. In a pediatric patient with Hemoglobin H disease, dysmorphic features and ID, 4 novel and clinically relevant Copy Number Variants were identified. PCR‐GAP, MLPA and FISH analyses established the cause of the α‐thalassemia. SNP‐array analysis revealed the presence of 4 altered loci: 3 deletions (arr[hg19]Chr16(16p13.3; 88, 165‐1, 507, 988) x1 ;arr[hg19]Chr6(6p21.1; 44, 798, 701‐45, 334, 537) x1 andarr[hg19]Chr17(17q25.3; 80, 544, 855‐81, 057, 996) x1 ) and a terminal duplication (arr[hg19]Chr7(7p22.3‐p22.2; 4, 935‐4, 139, 785) x3 ). The ‐α 3.7 mutation and the ∼1.51 Mb in 16p13.3 are involved in the alpha‐thalassemic phenotype. However, the critical region for ATR‐16 cannot be narrowed down. The deletion affecting 6p21.1 removes the first 2 exons and part of intron 2 of the RUNX2 gene. Although heterozygous loss of function mutations affecting this gene have been associated with cleidocranial dysplasia, the patient does not exhibit pathognomonic signs of this syndrome, possibly due to the fact that the isoform d of the transcription factor remains unaffected. This work highlights the importance of searching for cryptic deletions in patients with ID and reiterates the need of the molecular analysis when it is associated to microcytic hypochromic anemia with normal iron status. © 2016 Wiley Periodicals, Inc.